اقتراح طريقة فعالة لترتيب عملية الدخول للوسط لشبكات الحساسات اللاسلكية ذات بنية شجرة العناقيد والعاملة بالمعيار IEEE 802.15.4/Zig Bee حسب عامل الأولوية (Latakia University Journal -Engineering Sciences Series, 2019)
Wireless sensor networks became very common  in many different sides of  life, networks which have cluster tree topology with IEEE802.15.4/ Zig Bee shows high affection in many applications industrial ,healthy ,agricultural  and work is still progressive to improve performance of these networks and rise services quality. The arrangement to access medium is the most important door which can use it to improve the performance satisfy a requirement for renewing work. This effective arrangement will lead to organise slots reservation among super frame and to avoid collision and delay. Therefore, in this paper proposal method will be introduced to arrange the operation of mediumaccess according to priority factor,  in this way we can determine the appropriate slots according to the importance and priority of nodes which formed the networks, which allows to reduce power consumption and organising the traffic of packets according to their importance and reduce end to end delay, increase throughput and number of received packets at coordinator. أصبحت شبكة الحساسات اللاسلكية منتشرةً في مجالات الحياة المختلفة، وأبدت الشبكات ذات بنية شجرة العناقيد وفق المعيار IEEE 802.15.4 فعاليةً كُبرى في تطبيقاتٍ عديدةٍ زراعيةٍ وصناعيةٍ وصحيةٍ. ولا يزال العمل مستمراً لتحسين أداء عمل هذه الشبكات ورفع مستوى الخدمات. وتعدّ عملية الدخول للوسط من أهمّ الأبواب التي يمكن طرقها لتحسين الأداء تلبيةً لمتطلبات العمل المتجدّدة، حيث أنّ عملية الترتيب الفعالة ستؤدي لتنظيم عملية حجز الحيزات ضمن الإطار الرئيس وتفادي تصادم الإطارات والتأخير في تسليم الرزم. ولذلك تمّ تقديم اقتراح لترتيب عملية دخول العقد للوسط وفق عامل الأولوية، حيث يتمّ تحديد الحيزات المناسبة حسب أهمية وأولوية العقد المكوّنة للشبكة. مما يفسح المجال لتوفير استهلاك القدرة وتنظيم حركة تدفق الرزم حسب أهميتها، وتقليل التأخير الحاصل عند النهايات وزيادة انتاجية الشبكة من حيث عدد الرزم المستقبلة عند المنسق.